High-Resolution Computed Tomography Analysis of Variations of the Sphenoid Sinus - Tomovic, Senja; Esmaeili, Azadeh; Chan, Norman J.; Shukla, Pratik A.; Choudhry, Osamah J.; Liu, James K.; Eloy, Jean Anderson (Journal of Neurological Surgery Part B: Skull Base, 2013)
Purpose The sphenoid sinus is a complex structure with key variations that are important for endoscopic parasellar approaches. In this study, high-resolution computed tomography (HRCT) scans were analyzed for the frequency of these variations.Methods A retrospective radiographic analysis was conducted on patients undergoing HRCT between July 2008 and September 2010.Results Sphenoid sinus pneumatization was defined as conchal, presellar, sellar, and postsellar based on pneumatization relative to the anterior and posterior face of the sella. The distribution ranged from 1.8%, 7.3%, 47.6%, and 43.3%, respectively. We found a greater preponderance of sellar and postsellar variation than previously reported. No differences were found in regard to age, gender, and ethnicity (African American, Caucasian, Asian, and Hispanic) (p > 0.05). The prevalence of optic nerve, maxillary nerve, and internal carotid artery protrusion was 26.1%, 25.9%, and 28.2%, respectively, and dehiscence was 2.1%, 7.4%, and 2.9%, respectively. Accessory septae were present in 43.5% of cases. A lateral recess was identified in 72.4% and clinoid pneumatization in 20% of patients.Conclusion This study demonstrates a greater prevalence of sphenoid sinus pneumatization and variations than previously reported. This has important implications in terms of preparation and anticipation of possible variations to avoid complications.
Keywords: congdon classification; sphenoid sinus pneumatization; parasellar anatomy; endoscopic sinus surgery; sphenoid sinus; computed tomography; endoscopic skull base surgery; optic nerve; internal carotid artery; transsphenoidal surgery